Math

posted by .

[(6x+1)^3][(27x^2+2)-(9x^3+2x)](3)[(6x+1)^2](6) over [(6x+1)^3]^2

Help me simplify please? Here's what I got so far:

[(6x+1)^5]{(27x^2+2)-[x(9x^2+2)]}(18) over (6x+1)^6

It says in the back of the book (it's an odd problem that the answer is 27x^2-24x+2 over (6x+1)^4

Thanks!

• Math -

Oh, wait...It should actually be this (sorry!)

{[(6x+1)^3][(27x^2+2)}-{(9x^3+2x)](3)[(6x+1)^2](6)} over [(6x+1)^3]^2

Similar Questions

1. algebra

1)Simplify:(6x^3-16x^2+11x-5)/(3x-2) answer= 2x^2-4x+1-3over3x-2 2)Factor 27x^3-1 completley. answer= (3x-1)^3 if this isnt correct,im not sure how to solve it b/c this makes the most sense to me. 3)Simplify: x^2-3x-28 over x^2-9x+14,assume …
2. Algebra

checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4) + (-1)*3x + (-1)*(-4) = 6x*3x = 18x^2 6x*-4 = -24x -1*3x = -3x -1* -4 = 4 18x^2 – 24x -3x +4 = 18x^2 – 27x + 4
3. Math - Logarithmic

Solve: 2log_3(x) - log_3(x-2) = 2 My Work: log_3(x^2) - log_3(x-2) = log_3(3^2) log_3 [(x^2) / (x-2)] = log_3(27) (x^2) / (x-2) = 27 x^2 = (x-2)(27) x^2 = 27x - 54 x^2 - 27x = -54 27x = -54 x = -2 Textbook Answer: 3 or 6 Where did …
4. rational exponents

Express cube root 27x^4y^6 using rational exponents (27x^4y^6)1/3 (27^1/3)(x^4/3)(y^6/3) stuck. I think the final answer is 9x^3/4(y^2) I don't know where to put the parentheses to break it up so I hope yall understand what it's suppose …
5. Algebra (Intermediate)

5. Solve using the elimination method. Show your work. If the system has no solution or an infinite number of solutions, state this. 9x + 6y = 60 -27x Ð 18y = -180 Here's where I am at now: 9x(3) + 6y(3) = 60 27x +18y + 60 27 x + …
6. Math

I don't fully understand factorization in algebra. I've got a problem: 9x-27x^3. Can you please help me?
7. Math

factorize the following using. formula #1 : (x+y)^3 = x^3+3x^2y+3xy^2+y^2 formula #2 : (x-y)^3 = x^3-3x^2y+3xy^2-y^2 Problem #1 : 8a^3+60a^2+150a+125 Problem #2 : 27x^3-27x^2y+9xy^2-y^3 please tell me how to solve them
8. Integrated Math 1

The parabolas y = -3x2 + 10x - 6 and y = -3x2 - 17x + 2 intersect at _____?
9. Algebra 2

Can someone explain this exponential expression problem to me please?